The twelve lives of Samuel Hawley [compact disc, unabridged] : a novel - Tinti, Hannah (Brilliance Audio, 2017)
After years spent living on the run, Samuel Hawley moves with his teenage daughter, Loo, to Olympus, Massachusetts. There, in his late wife's hometown, Hawley finds work as a fisherman, while Loo struggles to fit in at school and grows curious about her mother's mysterious death. Haunting them both are twelve scars Hawley carries on his body, from twelve bullets in his criminal past, a past that eventually spills over into his daughter's present, until together they must face a reckoning yet to come.